1984
DOI: 10.1007/bf00252328
|View full text |Cite
|
Sign up to set email alerts
|

Combining abilities and heritability of callus formation and plantlet regeneration in wheat (Triticum aestivum L.) anther cultures

Abstract: Frequency of callus formation in wheat (Triticum aestivum L. em. Thell) anthers cultured in vitro and the frequency of subsequent plantlet formation from such calli were examined in a diallel population produced from five inbred spring wheat cultivars. Two of the five cultivars were believed to possess relatively high frequencies of response and the other three relatively low response frequencies, based on previous studies. General and specific combining abilities were estimated and found to be highly signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
56
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(70 citation statements)
references
References 13 publications
14
56
0
Order By: Relevance
“…Thus, genetic gain can be achieved if breeding strategies are designed for exploiting the anther culture response in indica rice. Similar results were reported by Lazar et al (1984) and Chaudhary et al (2003).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, genetic gain can be achieved if breeding strategies are designed for exploiting the anther culture response in indica rice. Similar results were reported by Lazar et al (1984) and Chaudhary et al (2003).…”
Section: Discussionsupporting
confidence: 91%
“…Many embryos and green plants were produced under such conditions as well (data not shown). Based on these findings, it seems that highly androgenic genotypes do exhibit a robust DH production and, as has been reported elsewhere, the heritability of this ability is relatively high (Lazar et al 1984;Opsahl-Ferstad et al 1994b;Moieni et al 1997). Andersen et al (1997) reported that 99.7% of the 913 green regenerants they screened were homozygous, a nearly identical finding to the 99.6% homozygosity observed in this study.…”
Section: Robustness Of Androgenic Capacitysupporting
confidence: 79%
“…The number of regenerated plants obtained is no way correlated to callus induction because this depends up on the friable embryogenic calli obtained from the total calli produced. These findings were agree with the previous reports in other crops like wheat (Lazar et al 1984), rye (Rakoczy-Trojanowska and Malepszy 1993) and barley (Ozgen et al 2005). Among 3 crosses between S. officinarumϫS.spontaneum, the F1 hybrids from AP1ϫAP2 and CP1ϫCP2 were found to have the best genetic background for callus induction frequency, culture efficiency, regeneration capacity and number of plants regenerated within the hybrids.…”
Section: Resultssupporting
confidence: 92%